2020
DOI: 10.1016/j.mser.2020.100562
|View full text |Cite
|
Sign up to set email alerts
|

Laser engineering of biomimetic surfaces

Abstract: The exciting properties of micro-and nano-patterned surfaces found in natural species hide a virtually endless potential of technological ideas, opening new opportunities for innovation and exploitation in materials science and engineering. Due to the diversity of biomimetic surface functionalities, inspirations from natural surfaces are interesting for a broad range of applications in engineering, including phenomena of adhesion, friction, wear, lubrication, wetting phenomena, self-cleaning, antifouling, anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
161
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(165 citation statements)
references
References 421 publications
(633 reference statements)
3
161
0
1
Order By: Relevance
“…Up-to-date surveys on this topic are found in recent reviews articles [ 2 , 3 , 4 , 5 ]. Many applications are particularly inspired by nature and enable surface engineering through tailored biomimetic laser-generated surface structures, reviewed in [ 6 , 30 ].…”
Section: Analysis Of the Research Area Of Lipssmentioning
confidence: 99%
See 2 more Smart Citations
“…Up-to-date surveys on this topic are found in recent reviews articles [ 2 , 3 , 4 , 5 ]. Many applications are particularly inspired by nature and enable surface engineering through tailored biomimetic laser-generated surface structures, reviewed in [ 6 , 30 ].…”
Section: Analysis Of the Research Area Of Lipssmentioning
confidence: 99%
“…Examples are dirt-repellent surfaces through the well-known lotus effect, anti-icing [ 57 , 58 ], the directional transport of liquids inspired by moisture-harvesting lizards [ 59 ] and bark bugs [ 60 ], antiadhesive surfaces inspired by cribellating spiders [ 61 ], or antibacterial [ 62 , 63 , 64 , 65 , 66 , 67 ], cell-repellent [ 68 ], and cell-stimulating/-adapting surfaces [ 69 , 70 , 71 ] for medical applications [ 72 ]. A detailed review of the laser engineering of biomimetic surfaces is provided in [ 6 ]. Combined processing strategies: Currently, several research groups are exploring the combination of LIPSS with additional surface treatment techniques—either “in situ” during the laser processing, or “ex situ” after the laser-processing.…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In recent years, the focus of experimental research has increasingly shifted toward the application of the gained knowledge aiming on the generation of tailored LIPSS for the creation of functional surface properties. [8][9][10][11][12][13][14] From the beginning, the experimental work was accompanied by theoretical studies on LIPSS formation, which is why today a large variety of model approaches is available that discuss the origin of LIPSS from sometimes very different perspectives. The objective of the present review article is to provide a systematic and comprehensive overview of the available LIPSS theories along with their historical context (Section 2), starting from the very first "simple" (a,b) Reproduced with permission.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the microstructures was ascribed to the cooperation of capillary waves and laser-induced etching (Vorobyev and Guo, 2013). With more explorations in this scheme, it has been found that fs laser direct-writing can induce four kinds of self-organized structures: ripples, microgrooves, microspikes, and hierarchical complex structures (Stratakis et al, 2020). These micro-nanostructures give rise to surface textures as well as hydrophobicity/superhydrophobicity, and morphologies are tunable by laser parameters such as laser fluence, pulse duration, and repetition rate (Vorobyev and Guo, 2013;Stratakis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%